A paraphyletic 'Silesauridae' as an alternative hypothesis for the initial radiation of ornithischian dinosaurs. (26th August 2020) - Müller, Rodrigo Temp; Garcia, Maurício Silva
Abstract : Whereas ornithischian dinosaurs are well known from Jurassic and Cretaceous deposits, deciphering the origin and early evolution of the group remains one of the hardest challenges for palaeontologists. So far, there are no unequivocal records of ornithischians from Triassic beds. Here, we present an alternative evolutionary hypothesis that suggests consideration of traditional 'silesaurids' as a group of low-diversity clades representing a stem group leading to core ornithischians (i.e. unambiguous ornithischians, such as Heterodontosaurus tucki ). This is particularly interesting because it fills most of the ghost lineages that emerge from the Triassic. Following the present hypothesis, the lineage that encompasses the Jurassic ornithischians evolved from 'silesaurids' during the Middle to early Late Triassic, while typical 'silesaurids' shared the land ecosystems with their relatives until the Late Triassic, when the group completely vanished. Therefore, Ornithischia changes from an obscure to a well-documented clade in the Triassic and is represented by records from Gondwana and Laurasia. Furthermore, according to the present hypothesis, Ornithischia was the first group of dinosaurs to adopt an omnivorous/herbivorous diet. However, this behaviour was achieved as a secondary step instead of an ancestral condition for ornithischians, as the earliest member of the clade is a faunivorous taxon. This pattern was subsequently followed by sauropodomorph dinosaurs. Indeed, the present scenario favours the independent acquisition of an herbivorous diet for ornithischians and sauropodomorphs during the Triassic, whereas the previous hypotheses suggested the independent acquisition for sauropodomorphs, ornithischians, and 'silesaurids'.